Saponification of Jatropha curcas Seed Oil: Optimization by D-Optimal Design - Jumat Salimon; Bashar Mudhaffar Abdullah; Nadia Salih (International Journal of Chemical Engineering)
In this study, the effects of ethanolic KOH concentration, reaction temperature, and reaction time to free fatty acid (FFA) percentage were investigated. D-optimal design was employed to study significance of these factors and optimum condition for the technique predicted and evaluated. The optimum conditions for maximum FFA% were achieved when 1.75 M ethanolic KOH concentration was used as the catalyst, reaction temperature of 65°C, and reaction time of 2.0 h. This study showed that ethanolic KOH concentration was significant variable for saponification of J. curcas seed oil. In an 18-point experimental design, percentage of FFA for saponification of J. curcas seed oil can be raised from 1.89% to 102.2%.